Arctic Monitoring and Assessment Programme (AMAP) work plan for 2017-2019 - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Council Secretariat, 2017)
The 2017-2019 AMAP work plan is developed within the context of a multiyear schedule for updating assessment of issues under AMAP's mandate. The 2017-2019 work plan reflects near-term priorities identified by the AMAP WG, taking note of Finnish Chairmanship priorities, in particular concerning environmental protection, education, and improved links to UN Sustainable Development Goals.